2017
DOI: 10.1111/gwat.12594
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Stream‐Aquifer Exchanges with Self‐Potential Measurements

Abstract: Characterizing the interactions between streams and aquifers is a major challenge in hydrology. Electrical self-potential (SP) is sensitive to groundwater flow through the electrokinetic effect, which is proportional to Darcy velocity. SP surveys have been extensively used for the characterization of seepage flow in a variety of contexts. But to our knowledge, a model coupling SP and groundwater flow has never been implemented for the study of stream-aquifer interactions. To address the issue, we first impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 73 publications
(123 reference statements)
0
9
0
Order By: Relevance
“…ERT consists of various VES distributed along a profile line, which allows a 2D interpretation of the resistivity distribution [47]. ERT has been successfully used to locate laterally varying geology, such as fracture zones, and to discriminate soil from bedrock [48][49][50]. In this study, we used 32 electrode sets having the same inter-electrode distance (5 m) along a line together with the computer and the TIGRE switch box, which automatically use almost all of the Wenner-Schlumberger electrode configurations among the 32 electrodes.…”
Section: Electrical Resistivity Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…ERT consists of various VES distributed along a profile line, which allows a 2D interpretation of the resistivity distribution [47]. ERT has been successfully used to locate laterally varying geology, such as fracture zones, and to discriminate soil from bedrock [48][49][50]. In this study, we used 32 electrode sets having the same inter-electrode distance (5 m) along a line together with the computer and the TIGRE switch box, which automatically use almost all of the Wenner-Schlumberger electrode configurations among the 32 electrodes.…”
Section: Electrical Resistivity Tomographymentioning
confidence: 99%
“…A significant contrast between peat and the underlying mineral soil will likely occur due to the markedly different physical characteristics of organic versus inorganic sediments [53]. Electrical resistivity depends on the water and clay content [50,54], as well as the media consolidation degree (Table 1).…”
Section: Electrical Resistivity Tomographymentioning
confidence: 99%
“…For saturated materials, the coupling coefficient is usually measured with the constant head flow experiment (e.g., Jackson & Vinogradov, 2012; Vinogradov et al., 2010); for unsaturated materials, the coupling coefficient is often measured indirectly with the transient flow experiment (e.g., Allègre, et al., 2010; Guichet et al., 2003; Jougnot & Linde, 2013; Mboh et al., 2012). Due to the direct coupling between water flow and electrical current flow, streaming potential measurements have been used in hydrology, for example, to detect preferential infiltration pathway (Jardani et al., 2007), reconstruct groundwater table (Jardani et al., 2009), and characterize stream‐aquifer exchanges (Valois et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations by [36,37] showed that fixed-reference land-based SP profiles, measured perpendicular to a river reach, can likely identify whether the river reach is losing, gaining, or flow-through, based on the polarity of the streaming-potential field in the surface-water relative to the polarity of the field on either side of the floodplain. However, fixed-reference SP surveys of surface-water gains and losses are generally impractical along reaches longer than a few river-kilometers because the fixed reference SP electrode must be continuously revisited and relocated, and because the SP electrodes must contact porous earth at every measurement location to complete an electrical circuit.…”
Section: Introductionmentioning
confidence: 99%